The gap between citizens and e-government projects: the case for Jordan. (16th July 2008) - Mofleh, Samer; Wanous, Mohammed; Strachan, Peter
Providing better services for citizens and responding to their growing demand for online needs have been major drivers for implementing e-government in developed countries. Many developing countries have also launched their e-government projects claiming that they are based on citizen-centric strategies. However, most developing countries have low internet penetration levels and their citizens do not have the capacity to use advanced e-services. Therefore, it can be questionable how these e-government projects are customer-centric. Are they responding to people's needs or just focusing on citizens' IT access? This research paper investigates Jordan's deployment of e government and examines how citizen-centric it is.